ANALISIS PENGARUH PENEGAKAN HUKUM TERHADAP PERKEMBANGAN CYBER CRIME - Humala Simangunsong (Jurnal Mantik Penusa, 2015)
This study is a normative legal research is descriptive with the approach of the law, which examines the laws and regulations related to legal issues raised and the approach of legal analysis, ie researchers will examine in depth review of the sound of the text of a legislation. The aim is to know the effect of law enforcement on the development of sybercrime. The type of data used is secondary data. Secondary data sources used include primary legal materials, secondary law materials and tertiary legal materials. Data collection techniques used are document studies or library materials. The study documents or library materials include efforts to collect data by visiting libraries, reading, reviewing and studying books, literature, articles, magazines, newspapers, scientific papers, papers, internet-related research objects. The results of the study indicate that the application of Indonesian positive law regulates crime in the virtual world such as in Article 281-283 of the Criminal Code (KUHP), Act No. 8 of 1992 on Film, Law Number 36 Year 1999 on Telecommunication, Article 5 Paragraph 1 and Article 13 Paragraph (1) Sub-Paragraph a of Law Number 40 Year 1999 concerning the Press, Article 36 Paragraph (5) of Law Number 32 Year 2002 on Broadcasting, Law Number 11 Year 2008 regarding Information and Transactions Electronic (UU ITE) and Law Number 44 Year 2008 regarding Pornography. The regulation is deemed inadequate when it is associated with the development of the Maya World Crime such as pornography on the internet now, its intercession is an unclear provision of pornography, the authorities to take certain actions in dealing with pornographic issues, the threat of too mild punishment, to account for crimes categorized as pornography, and inconsistent law enforcement.